Identification of Novel Conopeptides and Distinct Gene Superfamilies in the Marine Cone Snail Conus quercinus - Zhang, Han; Wang, Lei; Yang, Xiang; Lian, Zhiwei; Qiu, Yinbin; Dong, Zhanying; Wu, Xuedong; Pan, Xinghua (Frontiers in Marine Science, 2021)
Conopeptides from the marine cone snails are a mixture of cysteine-rich active peptides, representing a unique and fertile resource for neuroscience research and drug discovery. The ConoServer database includes 8,134 conopeptides from 122 Conus species, yet many more natural conopeptides remain to be discovered. Here, we identified 517 distinct conopeptide precursors in Conus quercinus using de novo deep transcriptome sequencing. Ten of these precursors were verified at the protein level using liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). The combined gene and protein analyses revealed two novel gene superfamilies (Que-MNCLQ and Que-MAMNV), and three other gene superfamilies (N, P, and I1) were reported for the first time in C. quercinus. From the Que-MAMNV superfamily, a novel conotoxin, Que-0.1, was obtained via cloning and prokaryotic expression. We also documented a new purification process that can be used to induce the expression of conopeptides containing multiple pairs of disulfide bonds. The animal experiments showed that Que-0.1 strongly inhibited neuroconduction; the effects of Que-1.0 were 6.25 times stronger than those of pethidine hydrochloride. In addition, a new cysteine framework (CC-C-C-C-C-C-CC-C-C-C-C-C) was found in C. quercinus. These discoveries accelerate our understanding of conopeptide diversity in the genus, Conus and supply promising materials for medical research.